EVALUATION OF THE CONTENT OF CD4+CD25+CD127LOW REGULATORY T CELLS AND THEIR FUNCTIONAL STATUS ACCORDING TO THE EXPRESSION OF CTLA-4 AND CD39 MOLECULES IN PATIENTS WITH RHEUMATOID ARTHRITIS - G. A. Zhulai; E. K. Oleinik; O. Yu. Barysheva; A. V. Churov; V. M. Oleinik; P. N. Kravchenko; A. A. Kuchin (Научно-практическая ревматология, 2014)
Objective. To study the content of the suppressor population of regulatory T cells (Treg) according to the expression of CD4, CD25, CD127 molecules, as well as the expression of two functional molecules (CTLA-4 and CD39) in patients with rheumatoid arthritis (RA). Material and methods. 16 samples of peripheral blood of RA patients and 10 blood samples of healthy donors were analyzed. All patients received disease-modifying anti-rheumatic drugs. The expression level of all studied molecules was assessed by flow cytofluorometry. Results. The content of T-helpers in peripheral blood of RA patients was 36.3 ± 7.1% of the total number of lympho- cytes and was lower than that in the control (43.8 ± 6.2%, p<0.05). The number of activated CD4+CD25+ T cells in these patients increased twofold (RA 23.7 ± 9.8%, control 11.1 ± 2.0% of the number of CD4+ T cells, p<0.05). The relative amount of CD4+CD25high (RA 2.7 ± 1.0%, control 1.5 ± 0.8%) and CD4+CD25highCD127low/- (RA 2.5 ± 1.0%, control 1.6 ± 0.9% of CD4+ T cells) Treg cells in RA patients was significantly higher than that in healthy individuals (p<0.05). The expression of the CTLA-4 negative regulatory molecule and CD39 ectonucleotidase by Treg cells of RA patients did not differ from the control. Conclusion. The study demonstrated that RA is characterized by an increased content of Treg cells of CD4+CD25high and CD4+CD25highCD127low phenotypes rather than CD4+CD25+CD127low, as well as by the control-like expression of CTLA-4 and CD39 functional molecules by Treg cells.